PERANCANGAN SISTEM KONTROL SUHU BEDPLATE DAN HOTEND PADA PRINTER 3D MODEL REPRAP - Tri Aji Saputra; Akhmad Musafa (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2020)
In this final project, a reprap model 3D printer has been designed. This system is designed so that the temperature of the 3D printer heater can work stably at the reference temperature for hotend 2000C and for the base plate with a reference temperature of 700C. The components used as heaters in this 3D printer are ceramic heater and NTC thermistor sensor. This tool consists of several components such as Arduino ATMega 2560, Ramps 1.4, stepper motor, Filament, hotend, and heatbed. For the printing process, a control system on the 3D printer heater is needed so that the filament can be evenly liquid. In this temperature control system uses two methods, the PID method and the On / Off method as a comparison to the quality of the printing results. When the heater on the 3D printer is energized according to the reference temperature, the sensor will measure the sensor readings and will be compared with the reference value. The results of the comparison are in the form of an error signal which will be processed on the PID controller. The output of the PID is in the form of a PWM signal which is used to heat the 3D printer. As for the controller using the On / Off method the output of the microcontroller is a high and low signal. When the sensor reads the temperature above the reference temperature, the output from the micro controller is a low signal. If the sensor reads the temperature below the reference temperature value, the output from the microcontroller is a high signal. The results of the comparison between the PID method and the On / Off method produce printing quality on a 3D printer with better results using the PID method. Because the temperature on the heater is more stable so that the melting results on the filament are relatively the same.